Non-invasive tissue erosion induced by high-intensity focused ultrasound - Poh, Poh Ling (2015)
High intensity focused ultrasound (HIFU) is a therapeutic modality that is becoming more widely used in clinical applications for treating tumours. Similar to the focusing of light, ultrasound waves can be focused at the intended specific part of a cancer. After focusing, the high levels of energy created in the HIFU beam can be magnified and subjected to a small volume with high precision. This treatment is usually non-invasive where adjacent tissues or cells are not affected by the treatment. However, research have to be done on the effects of non-invasive HIFU on growth of lesion, which is one of the obstacle in the acceptance of HIFU in clinical applications. In order to fully understand the effects of the parameters on formation on lesions, non-invasive HIFU was simulated and exposed to the gel phantoms. Subsequently, parameters such as pulse duration and flow rate were varied in order to determine each individual effects. After the experiments were done, it was observed that the lesions formed are cigar-shaped, and images of the lesions were captured using a digital camera. Analysis Pro (Olympus) program was used to analyse and calculate the lesion diameter and lesion length. It was found that an increase in pulse duration from 10ms to 20ms caused an increase in average lesion diameter and lesion length. Similarly, an increase in the internal channel flow rate resulted in an increase in average lesion diameter and lesion length. The results obtained provided an overview and direction for future work in the field of HIFU in clinical applications.